DESIGN ACCOUNTING RECORDING AND FINANCIAL REPORTING SYSTEM AT ANEKA PANCING STORE - Lisa Lim; Anita Anita (ConCEPt - Conference on Community Engagement Project, 2022)
The purpose of this research is to design an accounting recording and financial reporting system to reflect the actual business conditions for Aneka Pancing Store. So far, owner has only done manual accounting records in books where the owner faces difficulties in determining right profit or loss. Beside that, manual recording activities take a lot of time and it is difficult to track old data. This research will be start by observing and interviewing the person concerned to analyze the operational activities and existing problems deeply. Next, the author will carry out the implementation and evaluation process. The authors will design an accounting record system using the Microsoft Access program. The system is designed as starting from the user recording daily transactions which will become a database where the database will automatically generate financial reports. The financial reporting system is expected to assist in accurate and more efficient recording of operational activities. Hence the results of the financial statements are in accordance with applicable accounting standards.